Harry H. Woodring A Political Biography of FDR's Controversial Secretary of War - McFarland, Keith D. (University Press of Kansas, 1975)
The names of most of President Franklin D. Roosevelt's cabinet members are well known. Anyone familiar with FDR's administration will remember Henry Morgenthau, Jr., Cordell Hull, Harold Ickes, Frances Perkins, Henry Wallace, and James Farley. One member of that circle, however, has remained a virtual unknown: Harry H. Woodring, the recalcitrant Secretary of War who was forced by Roosevelt to resign from the cabinet.It is doubtful that the story of any of Roosevelt's cabinet members is more interesting than that of Woodring. With the breakdown of world peace in the 1930s, the matter of national defense became a major concern, and the United States military establishment became increasingly important. Woodring's role in Washington during this time was a critical one; his dealings with Roosevelt were extensive, and on many key issues his influence was considerable. Why, then, his lack of notoriety?The simple fact is that until now almost nothing has been written of Woodring's service as Secretary of War. He was one of the few individuals closely associated with Roosevelt who did not write an autobiography, memoirs, or some other personal account of what took place during those years. Keith D. McFarland is the first scholar to have had access to Woodring's personal papers. Drawing from this new material, as well as from Woodring's official correspondence and from personal interviews with the members of Woodring's immediate family and dozens of Woodring's associates, he provides in this volume the careful study that has long been needed.McFarland first traces Woodring's early political career in Kansas. As a Democratic Governor from 1931 to 1933, Woodring worked successfully with the Republicandominated legislature to alleviate many of the physical and economic hardships facing residents of the state during the Depression, Nevertheless, he lost his bid for reelection to Alf M. Landon. When Roosevelt won the presidency that same year, he appointed Woodring as Assistant Secretary of War.Woodring served the country well on the national level. He was influential to expanding the Army Air Corps and in making practical the Army's industrial and military mobilization plans. After the death of George Dern in 1936, Roosevelt demonstrated his confidence in Woodring by appointing him Secretary of War.The conflict between Woodring and the President arose over the sending of American military supplies and equipment to foreign nations. It was Woodring's job as secretary of War to see that the War Department adhered to the neutrality legislation of the 1930s. Roosevelt believed that the United States should aid the enemies of Hitler, even if such action did not adhere to the spirit of the neutrality legislation. Upon the outbreak of war in Europe in 1939, FDR did everything he could to supply Britain and France with American arms and munitions. Woodring was caught between is loyalty and devotion to the President and his sincere belief that the chief executive's program would endanger the nation's security. Maintaining that it was tactically unsound to give away supplies at a time when the U.S. Army was in desperate need of such items, Woodring made concerted efforts to prevent the implementation of FDR's program. The President was forced to ask him to resign.Few American Presidents have been more respected and admired than Franklin D. Roosevelt. There has been a tendency to disregard, ignore, or ridicule those administrative officials who disagreed with his actions and objectives. In relating the viewpoint of a distinguished, patriotic American who strongly opposed FDR's policies and tried to change them, this book provides a clearer understanding of politics and government in preWorld War II America.